Correlation of Hemoglobin A1C with Fasting Blood Plasma Glucose in Patients with Diabetes Mellitus and Its Implication as A Marker of Glucose Control - Sari, Putu Dyah Sartika; Arsana, I Nyoman; Juliasih, Ni Ketut Ayu (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus (DM) is a chronic disease whose prevalence continues to increase globally. Objective: This study aimed to analyze the correlation between hemoglobin A1c (HbA1c) and fasting blood plasma glucose (GDP) in patients with diabetes mellitus and its implications as a marker of glucose control. Method: A cross-sectional study was conducted using the medical records of 299 patients with diabetes mellitus (170 males and 129 females; age range: 19-90 years) treated at Bali Mandara Hospital from January to December 2022. Data on GDP levels and HbA1c values were collected and classified based on glycemic control. The correlation between GDP and HbA1c levels was tested using Spearman’s test. Results: The mean HbA1c value was not significantly different between the sexes and age groups, with higher values found in the 45-59 years age group and in women (7.88 ± 0.20%). The GDP ranged from 72-594 mg/dL, with a mean value of 181.45 ± 4.43 mg/dL. A significant positive correlation was observed between GDP and the HbA1c level (p<0.05). Poor glycemic control was found in 54.18% of the patients based on HbA1c and 69.23% based on GDP. Conclusions: Correlation between HbA1c levels and GDP is crucial for determining accurate and effective diabetes management strategies in clinical practice.